Community Value Co-Creation as a Catalyst for Village Tourism Sustainability: A New Paradigm - Noor , TB.Dicky Faldy Syahid; Hamsal , Mohammad; Abdinagoro , Sri Bramantoro; Raharjana, Destha Titi (Journal of Ecohumanism, 2024)
The purpose of this study is to propose a new conceptual model for tourism marketing management science, focusing on the perspective of the head of the tourist village manager to achieve village tourism sustainability. This study employs a quantitative approach and includes data from 140 respondents. The data pertains to the green environment mindset, local wisdom, community co-creation, and sustainable tourist villages. A quantitative research method was utilized in this study, with the head of the tourist village manager representing Indonesia. Data collected from 140 tourist village managers were analyzed using Smart PLS-4. This study's main findings emerged from the mediation hypothesis test results. Increasing community value co-creation, supported by the green environment mindset and local wisdom, contributed to sustainable tourist villages. This study adopts the perspective of service-dominant logic.